A utilização de redes definida por software: aplicações práticas do protocolo openflow - ALCÂNTARA JÚNIOR, Iacy Ribamar Gonçalves de (Instituto Federal do Amapá, 2021)
This Course Completion Work aimed to emulate a software-defined network and present, through a bibliographic reference, addressing the concepts, structure, composition and applications in the local environment. It was proposed to use a Mininet emulator, OpenvSwitch, integrated to the Ryu controller for deployment, of a series of test environment virtualized by VirtualBox, with diversified topologies, to demonstrate the management of the data flow through a switch with OpenFlow protocol.